PENGARUH TINGKAT PERTUMBUHAN, RASIO PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN OTOMOTIF DI INDONESIA) - B51111050, Vanny Pricilia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
The research aims to know the influence of firm growth, profitability and firm size to earning management. Firm growth measured by sales growth. Profitability measured by Net Profit Margin (NPM) and Return On Equity (ROE). Firm size measured by total assets and logaritma sales. Data are otomotive company listed in Indonesia Stock Exchange (IDX) year period 20010-2013. The samples in this research using the method of purposive. Based on sampling criteria the final sample in this research is 12 otomotive companies. This research use multiple linear regression analysis. The result of this research shows that firm growth, profitability and firm size no significant relationship to earning management. Keywords : Net Profit Margin (NPM), Return On Equity (ROE) and earning management.